Comparation Study of Wood Quality Influenced by Water Content with Ultrasonic Pulse Velocity Test Approach - Darmono, Darmono; Nugroho, Maris Setyo; Pamungkas, Rama Aji Pupus (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
In general, the building evaluation requires a sample from the building being tested. However, this cannot be done in cultural heritage buildings such as Masjid Gedhe Mataram. Because of that reason, an Ultrasonic Pulse Velocity test (UPV) is applied. This test aims to determine the strength of the wood quality due to the influence of its water content using the ultrasonic pulse velocity direct method. In the UPV test, the results are in the form of wave propagation which is influenced by several factors such as the type and the water content of the wood. There were 3 types of tested wood, 9 specimens each. The types of tested wood were kruing (KR), sengon (S), and teak wood (JTB). The water content was set at 12%, 15%, 20%, 25%, and 30%.The results showed a strong correlation between MoE and MoEd values of kruing wood with an R2 value of 0.8405, a weak correlation of sengon wood with an R2 value of 0.31, and a strong correlation of teak wood with an R2 value of 0.9331. The differences in wood quality based on modulus of elasticity between bending testing and UPV were 0.9 - 4.43% for kruing wood, 3.23 - 23.4% for sengon wood, and 3.4 - 33% for teak wood.